The Virtual Opera House: hybrid realities in lighting design processes for large-scale opera. Issue 4 (1st October 2020) - Hunt, Nick
ABSTRACT: Digital visualisation tools – virtual models – are increasingly used as part of the creative and production processes of large-scale theatre and opera. These technologies not only enable the modelling of the performance space with its scenic and lighting scenographies, but also facilitate the modelling of production processes and human relationships. Focusing on lighting at the Royal Opera House, London, I examine how digital visualisation allows designers and production teams to manipulate not only virtual space, but also virtual time. I show how the 'Virtual Opera House' allows multiple possible futures to be modelled, reviewed and selected. Further, the limited time available on the opera stage for lighting and technical rehearsals can be supplemented with additional, virtual stage rehearsals inserted between the physical ones: interstitial time. Away from the pressures of stage rehearsals, the lighting designer, lighting programmer and others spend time developing and nurturing the working relationships that are critical to the successful realisation of design intentions. Using primary evidence from practitioners, I demonstrate how the Virtual Opera House is not only a virtual model of the stage and physical production, but is also an environment where processes and relationships can be modelled and remodelled: a hybrid-reality collaborative environment.